(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2025)
Fossilised onomastic material in epigraphic or literary sources continues to constitute one of the main sources of information for the fragmentary languages of Western Europe, as is the case of Basque-Aquitanian and Continental Celtic dialects. The present work is articulated through the linguistic study of five Indo-European theonyms documented in the province of Aquitania (namely, OIDRITO, TELON[I], BORIENO, RANDOSATI, and VSSVBIO), that either had not previously received any attention or their etymologies are susceptible to criticism. These analyses will allow us to revisit some phonetic and morphological aspects of Gaulish and other Indo-European languages, as well as to shed new light on onomastic trends and cultic patterns common to different branches of the Indo European family.